2014
DOI: 10.1016/j.oraloncology.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the sensitivity and specificity of tissue-specific-based and anatomical-based optical biomarkers for rapid detection of human head and neck squamous cell carcinoma

Abstract: SUMMARY Objectives We propose the use of morphological optical biomarkers for rapid detection of human head and neck squamous cell carcinoma (HNSCC) by leveraging the underlying tissue characteristics in aerodigestive tracts. Materials and Methods Diffuse reflectance spectra were obtained from malignant and contra-lateral normal tissues of 57 patients undergoing panendoscopy and biopsy. Oxygen saturation, total hemoglobin concentration, and the reduced scattering coefficient were extracted. Differences in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…19 The diagnostic ability of the algorithm specific to buccal mucosa was steadfastly higher for discriminating benign, dysplastic, and malignant lesions. In a similar study, Hu et al 39 reported an increase in PPV and NPV when using tissue-specific classification algorithms, which resulted in the false-positive rates declining by 34%. The results from the present study indicate that site-specific algorithms implemented for the detection of lesions in the oral cavity increase diagnostic accuracy, which in turn reduces the number of false-negative rates.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…19 The diagnostic ability of the algorithm specific to buccal mucosa was steadfastly higher for discriminating benign, dysplastic, and malignant lesions. In a similar study, Hu et al 39 reported an increase in PPV and NPV when using tissue-specific classification algorithms, which resulted in the false-positive rates declining by 34%. The results from the present study indicate that site-specific algorithms implemented for the detection of lesions in the oral cavity increase diagnostic accuracy, which in turn reduces the number of false-negative rates.…”
Section: Discussionmentioning
confidence: 90%
“… 37 , 38 Improvements in the tissue classification parameters such as PPV and NPV were observed when site-specific classification was used to discriminate head and neck SCC. 39 To test this hypothesis on existing patient data, we collated data of patients with buccal mucosal abnormalities. We also recorded the DR ratio (R610/R545) from the left and right buccal mucosa of healthy volunteers with no history of alcohol, smoking, or tobacco usage.…”
Section: Resultsmentioning
confidence: 99%
“…Having established an appropriate, non-perturbative measurement device and technique, we sought to investigate HSNCC optical properties and identify potential diagnostic biomarkers. Significant differences in tissue hemoglobin saturation exist between cancerous and non-cancerous tissues; this has been seen in breast [ 26 ], rectum/anus [ 27 ] and head and neck cancer [ 28 ]. It is well-accepted that most solid tumors are both chronically and cyclically hypoxic due to the increase in oxygen demand and deficiencies in tumor vasculature [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies include incorporating optical filters for spectral imaging to estimate tumor hypoxia, a crucial cause for tumor angiogenesis [37], during the carcinogenesis. Measuring tumor hypoxia has shown promise for cancer detection [38][39][40]. Therefore, the addition of physiological endpoints to the currently available vascular features could potentially enhance the contrast between malignant and normal tissues.…”
Section: Discussionmentioning
confidence: 99%